Conflictos socioambientales y minería en Sonora, México - Lugo Gil , Crisel Yalitze; Lara Enríquez , Blanca Esthela (El Colegio de México A.C., 2022)
The state of Sonora is a national leader in mining production, but in 2014, it was the scene of a large-scale environmental disaster caused by the modern mining industry in Mexico. The objective of the article is to determine the actors and forms that socio-environmental conflicts have taken in the state, from 2008 to 2018. Our contribution was made to the systematization of 22 environmental contingencies and eight socio-environmental conflicts were catalogued. It is concluded that the forms of socio-environmental conflicts prior to the 2014 spill maintained local demands and the subsequent ones sought media visibility. The socio-environmental conflict of the Sonora River stands out for the diversity of actors and alliances.